Effects of naltrexone on alcohol self‐administration and craving: meta‐analysis of human laboratory studies - Hendershot, Christian S. (Addict Biol, 2016)
Randomized clinical trials have established the efficacy of naltrexone for reducing quantity of alcohol consumption and incidence of relapse to heavy drinking. To evaluate putative treatment mechanisms, human laboratory studies have examined naltrexone's effects on alcohol responses and self‐administration during short‐term medication protocols. Results from these studies are inconsistent and have yet to be examined in aggregate. This meta‐analysis aimed to quantify naltrexone's effects on alcohol self‐administration and craving in the context of placebo‐controlled human laboratory trials. Potential moderators of medication effects were also examined. Meta‐analyses of alcohol self‐administration (k = 9, N = 490) and craving (k = 16, N = 748) confirmed that, under controlled experimental conditions, naltrexone reduces the quantity of consumption (Hedges' g = −.277, SE = .074, 95 percent CI = −.421, −.133, p < .001) and magnitude of self‐reported craving (g = −.286, SE = .066, 95 percent CI = −.416, −.156, p < .001) relative to placebo. Subgroup and moderation analyses found no evidence that effect sizes differed by study population (dependent versus non‐dependent drinkers), laboratory paradigm or duration of medication exposure. These results substantiate prior evidence for reductions in event‐level craving and consumption as potential treatment mediators, also establishing effect sizes to inform future human laboratory trials. From a clinical perspective, these results may provide additional evidence regarding naltrexone's efficacy in the context of acute or subacute dosing regimens.